Tracking productivity: Companies are taking advantage of their new ability to snoop on their workers—and their customers. (Economist, 2019)
The article explains the ability of companies to snoop on their workers and customers. They have deployed the Internet of things (IoT) such as sensors and distributed computing. According to research firm GSMA Intelligence, consumer uses of the IoT will be overtaken by industrial ones by 2023. Insurance companies have taken advantage of the surveillance capabilities offered by connected gadgets.